Selection Of Raw Materials For Leather Jacket Using The Analytical Hierarchy Process (Ahp) Method - et. al., Didit Damur Rohman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cow leather, sheep leather, goat leather and buffalo leather are the raw materials for making leather jackets at PT X umkm. The selection of raw materials determines the quality of the leather jacket product with the appropriate criteria to meet quality standards. PT X has determined the best criteria in the production of leather jackets including physical, color, texture and moisture content as parameters for determining decision making. The end result of this study is which leather type best fits the required criteria. Determination of alternative choices for leather jacket raw materials using the Analytical Hierarchy Process (AHP) method. Determining the texture and moisture content is a decision that can be obtained for the multicriteria decision making materials for choice and identification of problems to develop in finding or formulating alternative problems using the Analytical Hierarchy Process method ( AHP) documentation from a library study from the calculation of cowhide with the results obtained that cow leather ranks first in all aspects of the criteria, starting from physical criteria, color, texture, and moisture content, with these results cowhide is in a higher texture and content. superior with total weight of cow leather1.66, sheep leather 1.07, goat leather 0.84 and buffalo leather 0.43. However, research continues to improve the addition of criteria and alternatives in the hope of increasing choices.